Influence of glutamine synthetase gene polymorphisms on the development of hyperammonemia during valproic acid-based therapy. (December 2015) - Inoue, Kazuyuki; Takahashi, Toshiki; Yamamoto, Yoshiaki; Suzuki, Eri; Takahashi, Yukitoshi; Imai, Katsumi; Inoue, Yushi; Hirai, Keita; Tsuji, Daiki; Itoh, Kunihiko
Highlights: 9.9% of patients exceeding 200 μg/dL ammonia during VPA-based therapy. 14.9% of patients exceeding 170 μg/dL ammonia during VPA-based therapy. GLUL rs10797771 polymorphism was a risk factor for exceeding 200 μg/dL ammonia level. Phenytoin coadministration was a risk factor for exceeding 200 μg/dL ammonia level. Female gender was a risk factor for exceeding 170 μg/dL ammonia level. Abstract: Purpose: Valproic acid (VPA), which is widely used to treat epilepsy, migraine, and bipolar disorder, can causes severe hyperammonemia. However, the mechanism responsible for this adverse effect is not readily apparent. We previously reported that phenytoin coadministration is a strong risk factor for the development of hyperammonemia during VPA-based therapy. In this study, we focused on glutamine synthetase, which catalyzes the synthesis of glutamine from glutamate and ammonia and examined the association with the development of hyperammonemia during VPA-based therapy. Methods: For this study, we recruited 202 Japanese pediatric patients having epilepsy. We selected three polymorphisms (rs10911070, rs10797771, and rs10911021) in the glutamine synthetase (GLUL) gene. Hyperammonemia was defined as a plasma ammonia level exceeding 200 or 170 μg/dL. We evaluated the association between the development of hyperammonemia during VPA-based therapy and the patient characteristics, including three GLUL polymorphisms. Results: The number of patients who developed hyperammonemia during VPA-based therapy was 20 (9.9%) using the 200 μg/dL cutoff value and 30 (14.9%) using the 170 μg/dL cutoff value. Using a multivariate logistic regression analysis, the GLUL rs10797771 polymorphism and phenytoin coadministration in the 200 μg/dL cutoff value, and female in addition to two factors in the 170 μg/dL cutoff value, had significant associations with a plasma ammonia level elevation during VPA-based therapy. Conclusion: Phenytoin coadministration, GLUL rs10797771 polymorphism in the 200 μg/dL cutoff value, and female in addition to two factors in the 170 μg/dL cutoff value, are independent risk factors for elevated plasma ammonia levels during VPA-based therapy.